A new ent-kaur-16-en-19-oic acid from the aerial parts of Inula bifrons. (December 2020) - Ivanova, Victoria; Todorova, Milka; Aneva, Ina; Nedialkov, Paraskev; Trendafilova, Antoaneta
Abstract: The phytochemical study of the chloroform extract of the aerial parts of Inula bifrons (L.) L. led to the isolation of one new ent -kaurane diterpenes acid along with twelve known compounds (two ent -kaurane diterpenoids, an eudesmane acid, five sesquiterpene lactones, three triterpenoids and β -sitosterol). All known compounds are found for the first time in I. bifrons . Their structures were elucidated by using spectral methods (NMR, HRESIMS and IR). The distribution of these compounds in the genus Inula and their chemotaxonomic significance is discussed. Graphical abstract: Image 1 Highlights: The chloroform extract from the aerial parts of Inula bifrons was studied. The structure of a new ent -kaur-16-en-19-oic acid was determined by NMR and HRESIMS. In addition, twelve known compounds were reported for the first time in I. bifrons. The chemotaxonomic significance of the isolated compounds is discussed.